The Effect of Acknowledged and Novel Anti-Rheumatic Therapies on Periodontal Tissues-A Narrative Review - Maria-Alexandra Martu; George-Alexandru Maftei; Ionut Luchian; Ovidiu Mihail Stefanescu; Mihaela Monica Scutariu; Sorina Mihaela Solomon (MDPI AG, 2021)
Rheumatoid arthritis (RA) and periodontal disease (PD) are chronic complex inflammatory diseases with several common susceptibility factors, especially genetic and environmental risk factors. Although both disorders involve a perturbation of the immune-inflammatory response at multiple levels, one major difference between the two is the different locations in which they develop. RA is triggered by an exaggerated autoimmune response that targets joints, while periodontal disease occurs as a consequence of the subgingival periodontopathogenic microbiota. Current treatment models in both pathologies involve the stratification of patients to allow therapeutic individualization according to disease stage, complexity, progression, lifestyle, risk factors, and additional systemic diseases. Therapeutic guidelines for RA comprise of five main classes of drugs: non-steroidal anti-inflammatory drugs (NSAIDs), analgesics, glucocorticoids, and disease-modifying anti-rheumatic drugs (DMARDs): biologic and non-biologic. Although various treatment options are available, a definitive treatment remains elusive, therefore research is ongoing in this area. Several alternatives are currently being tested, such as matrix metalloproteinases (MMP) inhibitors, toll-like receptors (TLR) blockers, pro-resolution mediators, anti-hypoxia inducing factors, stem cell therapy, NLRP3 inhibitors and even natural derived compounds. Although the link between PD and rheumatoid arthritis has been investigated by multiple microbiology and immunology studies, the precise influence and causality is still debated in the literature. Furthermore, the immunomodulatory effect of anti-rheumatic drugs on the periodontium is still largely unknown. In this narrative review, we explore the mechanisms of interaction and the potential influence that anti-rheumatoid medication, including novel treatment options, has on periodontal tissues and whether periodontal health status and treatment can improve the prognosis of an RA patient.